Effects of Natural Sorbents on the Germination and Early Growth of Grasses on Soils Contaminated by Potentially Toxic Elements - Ingrid Turisová; Tatiana Kviatková; Katarzyna Możdżeń; Beata Barabasz-Krasny (Plants, 2020)
The reclamation of abandoned mining heaps rich in potentially toxic elements (PTEs) is critical for the environment. We carried out a laboratory experiment studying the effects of the addition of four natural sorbents (biochar, bentonite, chicken manure and organo-zeolitic substrate) to soils contaminated with PTEs, predominantly Cu, As and Sb, on the germination and growth of the autochthonous grasses Agrostis capillaris, A. stolonifera, Festuca rubra and Poa pratensis. The experiment used Petri dish tests with water extracts of contaminated soil and soil neutralised with the four sorbents. Standard indexes of the germination process were used (germination percentage, time required for 50% germination index, speed of emergence), and different values were found depending on the plant species and sorbent used. However, the percentage of seeds germinating was lower for each sorbent compared to the control (distilled water). The fresh mass values were positively stimulated by all sorbents. Electrolyte leakage was the highest in seedlings watered with an extract of untreated soil from the heap compared to extracts from treated soils and the control. This can be interpreted as eliminating the harmful effects of increased potentially toxic element (PTE) contents by sorbents, which can be useful in remediation processes.